Māori oral histories and the impact of tsunamis in Aotearoa-New Zealand - D. N. King; D. N. King; W. S. Shaw; P. N. Meihana; J. R. Goff; J. R. Goff (Natural Hazards and Earth System Sciences, 2018)
Māori oral histories from the northern South Island of Aotearoa-New Zealand provide details of ancestral experience with tsunami(s) on, and surrounding, Rangitoto (D'Urville Island). Applying an inductive-based methodology informed by <q>collaborative storytelling</q>, exchanges with key informants from the Māori kin groups of Ngāti Koata and Ngāti Kuia reveal that a <q>folk tale</q>, published in 1907, could be compared to and combined with active oral histories to provide insights into past catastrophic saltwater inundations. Such histories reference multiple layers of experience and meaning, from memorials to ancestral figures and their accomplishments to claims about place, authority and knowledge. Members of Ngāti Koata and Ngāti Kuia, who permitted us to record some of their histories, share the view that there are multiple benefits to be gained by learning from differences in knowledge, practice and belief. This work adds to scientific as well as Maōri understandings about tsunami hazards (and histories). It also demonstrates that to engage with Māori oral histories (and the people who genealogically link to such stories) requires close attention to a politics of representation, in both past recordings and current ways of retelling, as well as sensitivities to the production of <q>new</q> and <q>plural</q> knowledges. This paper makes these narratives available to a new audience, including those families who no longer have access to them, and recites these in ways that might encourage plural knowledge development and co-existence.